Komunitas Basis di Pusaran Globalisasi: Bermisi di Tengah Kemajuan Zaman - Wotan, Fidelis B. (Perspektif, 2011)
Globalization nowadays affects human mentality and lifestyle. Humans have experienced a remarkable acceleration, due to development and technology, as well as deterioration in mental attitude - people become lazy, individualistic, hedonist, consumerist, and more marginalized poor. It challenges the Church's way of doing mission. The article tries to elaborate mission through creating and planting mission spirituality in the basic communities. Basic communities have some characteristics: communion, ecclesiastic, and laypeope-based, living from the Word and the Eucharist. The goal is faith planting (plantatio fidei). Each basic community is expected to be a crutch to deal with individualism, hedonism, creating a culture of solidarity, to be critical and transformative, creating awareness for a better world. Pastoral recommendations are suggested here: doing mission from within, namely participatory theology; building a counterculture, namely Christian communities mark Christ's presence in the world.